Management of Al-Islam of Muhammadiyah and Arabic Language Education Curriculum (ISMUBA) at Muhammadiyah College Schools in Central Balikpapan - Kasim, Mat; Hasanah, Enung; Sukirman, Sukirman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
ISMUBA subjects in Muhammadiyah schools are important to equip students with strong moral and ethical values, as well as to strengthen their understanding of the Muhammadiyah movement. However, in its implementation, it is still constrained by the minimal use of learning media, where teachers rely more on lecture methods. The purpose of this study was to determine the management of the ISMUBA Curriculum at Muhammadiyah Schools in Central Balikpapan. This study is a qualitative study with a descriptive type. Data collection techniques used observation, interview, and documentation techniques at Muhammadiyah Middle and High Schools in Central Balikpapan. Data analysis techniques used qualitative analysis techniques. The results of this study indicate that the planning of ISMUBA Curriculum Management at Muhammadiyah Schools in Central Balikpapan was carried out by considering the needs and development of students. The curriculum was designed by a development team under the Muhammadiyah Elementary and Secondary Education Council with the aim of maintaining the quality of education and was arranged flexibly to be relevant to the conditions of each school. The organization of ISMUBA Curriculum Management involves cooperation between the Muhammadiyah Elementary and Secondary Education Council and ISMUBA teachers through the Subject Teacher Deliberation (MGMP). The curriculum structure includes intracurricular, co-curricular, and extracurricular activities that function to support the holistic development of students. ISMUBA Curriculum Management combines classroom learning methods with Islamic values habituation activities, such as dhuha prayer and Quran memorization. The use of technology in learning has begun to be implemented, although there are obstacles related to limited facilities. ISMUBA Curriculum Management Evaluation is carried out comprehensively by assessing students' attitudes, knowledge, and skills through observation, project, and portfolio methods.